The nature and modelling of piospheres: a review - I. Thrash; J.F. Derry (Koedoe: African Protected Area Conservation and Science, 1999)
Gradients in utilisation pressure tend to develop around watering points because water dependent herbivores are forced to congregate within a maximum distance of about 10-15 km from water in the dry season. Artificial watering points cause previously migratory or nomadic indigenous large herbivores to become sedentary, so that natural grazing patterns are disrupted. Under this altered grazing pattern, piosphere patterns tend to develop in herbaceous species composition, range condition, grass production, plant biomass, understory cover, standing crop and basal cover. In areas with large populations of elephants the density and canopy cover of trees is directly proportional to distance from watering points. In the absence of elephants an increase in woody plant density and canopy cover tends to occur in a zone just beyond a sacrifice area. Soil erosion, compaction and capping tend to occur at watering points on soils containing clay and silt. Artificial watering points are advantageous to the non-mobile water dependent large herbivore species and disadvantageous to the water independent large herbivore species. The processes underlying piosphere development and maintenance are numerous and diverse. While being parsimonious treatments of a complex system, conceptual models do provide a reasonable basis upon which to design an improved understanding. The logistic curve has been proposed as a convenient tool for estimating piosphere dimensions, but ignoring the 'best-fit' regression model for a piosphere data set may be an inaccurate practice. A large number of gradient models have been developed, each an attempt to shed some light on the behavioural response underlying what appears to be a complex grazing pattern. Several system models that take piosphere effects into account have been constructed. Some of these produce good simulations of herbaceous materi- al dynamics and especially good simulations of bush dynamics.